2013
DOI: 10.3390/md11093109
|View full text |Cite
|
Sign up to set email alerts
|

Pachydictyols B and C: New Diterpenes from Dictyota dichotoma Hudson

Abstract: Two new diterpenoids, pachydictyol B (1a/1b) and C (2), were isolated from the dichloromethane extract of the marine brown alga, Dictyota dichotoma, collected from the Red Sea coast of Egypt, along with the known metabolites, pachydictyol A (3a), dictyol E (4), cis-africanan-1α-ol (5a), fucosterol (6), tetrahydrothiophen-1,1-dioxide and poly-β-hydroxybutyric acid. GC-MS analysis of the nonpolar fractions also indicated the presence of β-bourbonene and nonanal, along with three hydrocarbons and five fatty acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…In another study, dichloromethane extract of D. dichtoma was found to have an IC 50 of 600 ng mL -1 in MCF-7 cell line, a concentration 35 fold higher than what we have determined. Since the same cell line is used in both studies, the difference should be attributed to the extraction method used which is Soxhlet extraction for the mentioned study (Abou-El-Wafa et al 2013). Another member of Dictyotaceae family, Dictyota Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, dichloromethane extract of D. dichtoma was found to have an IC 50 of 600 ng mL -1 in MCF-7 cell line, a concentration 35 fold higher than what we have determined. Since the same cell line is used in both studies, the difference should be attributed to the extraction method used which is Soxhlet extraction for the mentioned study (Abou-El-Wafa et al 2013). Another member of Dictyotaceae family, Dictyota Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Error bars represent standard deviation cilliolata, was also tested for its anticancer potential in different cell lines including MCF-7 (Caamal-Fuentes et al 2014) and in this study, the extract was effective only at microgram per mL concentrations. Furthermore in several studies focusing on the anti-cancer potential of pure compounds isolated from Dictyota species in different cell lines including MCF-7, IC 50 values calculated for all of the compounds were at microgram per mL scale (Jongaramruong and Kongkam 2007;Ayyad et al 2011;Abou-El-Wafa et al 2013;Pardo-Vargas et al 2014). Since our extract was much more effective compared to all counterparts and to all pure compounds mentioned, we believe either the extract itself or the active compounds of the extract have a strong potential to be used as anti-cancer agent.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies reported that the crude extract of D. dichotoma exhibited strong cytotoxicity to various human cancer cell lines including Daudi, Jurkat, HEp-2, and K562 (human leukemic cell) and demonstrated the cytotoxic activity of D. dichotoma to be superior to that of other species of brown algae including Bifurcaria bifurcata, Cystoseira tamariscifolia, Fucus ceranoides, and Halidrys siliquosa [15,26]. In fact, D. dichotoma has been shown to be a potent cancer inhibitor as it exhibited a remarkably low IC 50 value of 0.6 μg/mL against MCF-7 cells [16]. Other species of brown algae including Himantothallus grandifolius suppressed proliferation and promoted apoptosis-mediated cell death in various epithelial tumor cell lines (i.e., A-549, A-375, HEp-2, and HeLa) [27].…”
Section: Cytotoxic Activity Against Cancer Cell Linesmentioning
confidence: 99%
“…Dictyota dichotoma (D. dichotoma) and four other brown algae species: Bifurcaria bifurcata, Cystoseira tamariscifolia, Desmarestia ligulata, and Halidrys siliquosa have exhibited a substantial cytotoxic activity to three cancer cell lines: Daudi (human Burkitt's lymphoma), Jurkat (human leukemic T cell lymphoblast), and K562 (human chronic myelogenous leukemia) [15]. Moreover, the crude extract of D. dichotoma isolated from the Egyptian Red Sea coast exerted a potent cytotoxic effect on breast carcinoma tumor cell line MCF7 [16]. e complexity, poor prognosis, and patient specificity, type specificity, and stage specificity of cancer require the investigation and identification of novel compounds with effective clinical utility.…”
Section: Introductionmentioning
confidence: 99%
“…Dictyota is particularly rich in bioactive terpenes (Viano et al 2009;Othmani et al 2014;da Gama et al 2014) of which some have an established potential for anti-fouling coatings, thanks to their algicidal (Kim et al 2006), anti-bacterial (Enoki et al 1983) and anti-fungal (Tringali et al 1986) and molluscicidal activity (Tringali et al 1986; Barbosa et al 2007). Dictyotalean diterpenes also have been identified as potential therapeutic options for different pathologies (Abou-El-Wafa et al 2013;Caamal-Fuentes et al 2014), HIV-1 and HSV-1, thanks to their anti-retroviral (Pereira et al 2004;Abrantes et al 2010;Cavalcanti et al 2011;Miceli et al 2012;Zhou et al 2013), anti-leishmaniasis (Soares et al 2012) and anti-malarial activity (Jongaramruong and Kongkam 2007) and their role as anti-coagulants (De Andrade et al 2014). Crude extracts of Dictyota have been shown to be effective against cancer cells (Gomes et al 2015).…”
Section: Introductionmentioning
confidence: 99%